Locating the solar source of 13 April 2006 magnetic cloud - K. Steed; C. J. Owen; L. K. Harra; L. M. Green; S. Dasso; A. P. Walsh; P. Démoulin; L. van Driel-Gesztelyi; L. van Driel-Gesztelyi; L. van Driel-Gesztelyi (Annales Geophysicae, 2008)
Using Advanced Composition Explorer (ACE) in situ data we identify and describe an interplanetary magnetic cloud (MC) observed near Earth on 13 April 2006. We also use multi-instrument and multi-wavelength observations from the Solar and Heliospheric Observatory (SOHO), the Transition Region and Coronal Explorer (TRACE) and ground-based solar observatories to determine the solar source of this magnetic cloud.